Mortality and quality of life after proximal femur fracture: effect of time until surgery and reasons for delay - Muhm, Markus Joachim; Arend, G.; Ruffing, Thomas; Winkler, Hartmut (European journal of trauma and emergency surgery, 2013)
Studies yield conflicting results from the effect of early surgery on mortality. Some observed a positive, others a negative and some did not find any effect of early operation. In this study, mortality and quality of life in relation to time until surgery as well as reasons for delay were observed prospectively.